TECHNO-ECONOMIC ANALYSIS OF THE NATURAL GAS PIPELINE CONSTRUCTION AND REFINING PROCESS FROM GREATER SUNRISE OFFSHORE TO NATARBORA ONSHORE, TIMOR-LESTE - Francisco Manuel Gusmao; Sutrasno Kartohardjono (RADJA PUBLIKA, 2026)
The Greater Sunrise gas field, with a production capacity of 750 MMSCFD, is a strategic energy source for Timor-Leste. Its development is planned through an offshore refining facility and a 250 km pipeline to Natarbora, requiring comprehensive technical and economic studies. Technically, gas purification is carried out to remove CO₂, H₂S, heavy hydrocarbons, and water vapor to prevent corrosion, hydrate formation, and equipment damage during transportation. The processes used include a three-phase separator, acid gas separation (Acid Gas Removal Unit, AGRU), heavy hydrocarbon separation (Dew Point Control Unit, DPCU), and a water separation unit. Simulation results show that the gas is dominated by 85.1% methane, with the AGRU able to reduce CO₂ from 0.05 to 0.02, resulting in a marketable gas of 724.4 MMSCFD. At the DPCU with a flow rate of approximately 723 MMSCFD, it produces 11 barrels/day of condensate, and the dehydration process produces 723 MMSCFD of dry gas. Economically, a 24-inch diameter pipe was chosen as the most optimal option with a compressor requirement of 5 units. The total CAPEX of the project is 3,337 million USD with OPEX of 51 million USD, including the cost of the pipe, vessel installation, compressor, platform, and gas purification facilities. Based on the results of the gas price sensitivity calculation of 4-10 USD/MMBTU, the project is not feasible at a price of 4-5 USD/MMBTU, which is indicated by a negative NPV, IRR of 2-9%, and a Payback Period of 10-17 years. The project begins to be feasible at a price of 6 USD/MMBTU with an NPV of 1040 million USD, an IRR of 16%, and a Payback Period of 4 years. Furthermore, at a price of 7-10 USD/MMBTU, economic performance improves significantly, with an NPV of up to 6102 million USD, an IRR of up to 47%, and a shorter payback period of 1-3 years. At a gas price of around 7 USD/MMBTU, the project is declared economically feasible and prospective.